Next Generation Strategies for Geroprotection via mTORC1 Inhibition. (22nd February 2019) - Dumas, Sabrina N; Lamming, Dudley W
Abstract: Inhibition of mTORC1 (mechanistic Target Of Rapamycin Complex 1) with the pharmaceutical rapamycin prolongs the lifespan and healthspan of model organisms including rodents, with evidence now emerging that rapamycin and its analogs may also have rejuvenative effects in dogs and humans. However, the side effects associated with long-term rapamycin treatment, many of which are due to inhibition of a second mTOR complex, mTORC2, have seemed to preclude the routine use of rapamycin as a therapy for age-related diseases. Here, we discuss recent findings suggesting that strong, chronic inhibition of both mTOR complexes may not be necessary to realize the geroprotective effects of rapamycin. Instead, modestly but specifically inhibiting mTORC1 via a variety of emerging techniques, including intermittent or transient treatment with rapamycin derivatives, or specific dietary regimens, may be sufficient to promote health and longevity with reduced side effects. We will also discuss prospects for the development of new molecules that, by harnessing the detailed molecular understanding of mTORC1 signaling developed over the last decade, will provide new routes to the selective inhibition of mTORC1. We conclude that therapies based on the selective inhibition of mTORC1 may soon permit the safer treatment of diseases of aging.